Chemometric characterization of the trace element profile of raw meat from Rubia Gallega x Holstein Friesian calves from an intensive system. (March 2019) - Gálvez, F.; López-Alonso, M.; Herrero-Latorre, C.; Miranda, M.; Franco, D.; Lorenzo, J.M.
Abstract: This study was conducted to compare the essential and toxic element content of seven veal cuts: shoulder clod (SC), inside round (IR), eye of round (ER), bottom round (BR), heel of round (HR), knuckle (KK) and tenderloin (TL). Eighty-four meat samples were determined by ICP-MS. Overall, essential trace elements (Co, Cu, Fe, Mn and Zn), except Se, varied significantly between the different meat cuts. By contrast, there were no significant variations for the minor trace elements (Cr, Mo and Ni) or the toxic elements (As, Cd and Pb). Chemometric analysis of the data identified four clusters: (1) the main trace elements, except (2) Se, which was closely related to (3) the toxic elements, and finally (4) the minor trace elements. TL and ER cuts constituted two separated groups; most of the SC and KK samples were associated, and IR and BR samples overlapped. TL and SC contained the highest amounts of trace elements, whereas ER and KK the lowest. Highlights: We evaluate the essential and toxic elements in seven veal cuts. The main essential trace elements, except Se, vary significantly between the meat cuts. Chemometric analysis of the data identify four clusters of elements. Tenderlion and shoulder clod contain the highest amounts of trace elements. Trace element profiles could be used to establish the nutritional value of meat cuts.